GEJALA DIAGNOSTIK DAN REMEDIAL PADA ANAK DIDIK DI PENDIDIKAN DASAR/MADRASAH IBTIDAIYAH - Rusiadi Rusiadi; Aslan Aslan (Borneo : Journal of Islamic Studies, 2021)
Remedial activities held in every subject at every level of education, including elementary school or madrasah Ibtidaiyah do not affect the curriculum's changes at every school level. Because curriculum changes are only changes in the system, materials, and teaching methods, remedial is to overcome problems experienced by students in mastering each subject at the end of the semester of the lesson program. This research is library research by collecting various pieces of literature under the research study. The research results include; First, remedial learning is carried out to students because of the problem of weakness in receiving subjects to implement the remedial. However, these activities are following the problems experienced by students. Second, when students experience problems, the teacher's job is to map the problems experienced with two criteria: remedies carried out to catch up with lesson content before proceeding to the next class level